Clinical considerations for use of insulin degludec/insulin aspart in Japanese patients. (2nd January 2018) - Hirose, Takahisa; Awata, Takuya; Yamamoto, Yuiko; Hemmingsen, Mads Peter
ABSTRACT: Introduction : Co-formulation of basal and bolus insulin components provides a simpler regimen for patients with type 2 diabetes than separate basal–bolus treatment. However, conventional premixed insulin products include a suboptimal protaminated basal component that requires resuspension prior to injection. Insulin degludec/insulin aspart (IDegAsp) is the first soluble co-formulation of a basal insulin with an ultra-long duration of action (IDeg) and a rapid-acting bolus insulin (IAsp) in a single injection. Areas covered : In this review, the authors summarize findings from pre-clinical studies and the clinical trial program and provide guidance for the initiating and switching of IDegAsp in different patient populations. Pharmacodynamic analyses have revealed a rapid onset of action and distinct peak (IAsp), followed by a separate, flat and stable basal effect (IDeg component). Phase 3 studies have demonstrated the efficacy and safety of IDegAsp, with greater glycemic improvements than basal-only therapy in international and Japanese type 2 diabetes populations. IDegAsp also results in reduced insulin dose requirements and lower rates of hypoglycemia than premixed insulin. Expert opinion : IDegAsp provides a simple and effective insulin regimen in appropriately selected Japanese patients, with the flexibility to suit individual needs. The benefits of IDegAsp over conventional insulin regimens might help tackle clinical inertia with insulin intensification.